SerpinB2 Regulates Immune Response in Kidney Injury and Aging - Sen, Payel (J Am Soc Nephrol, 2020)
BACKGROUND: Expression of SerpinB2, a regulator of inflammatory processes, has been described in the context of macrophage activation and cellular senescence. Given that mechanisms for these processes interact and can shape kidney disease, it seems plausible that SerpinB2 might play a role in renal aging, injury, and repair. METHODS: We subjected SerpinB2 knockout mice to ischemia-reperfusion injury or unilateral ureteral obstruction. We performed phagocyte depletion to study SerpinB2’s role beyond the effects of macrophages and transplanted bone marrow from knockout mice to wild-type mice and vice versa to dissect cell type–dependent effects. Primary tubular cells and macrophages from SerpinB2 knockout and wild-type mice were used for functional studies and transcriptional profiling. RESULTS: Cultured senescent tubular cells, kidneys of aged mice, and renal stress models exhibited upregulation of SerpinB2 expression. Functionally, lack of SerpinB2 in aged knockout mice had no effect on the magnitude of senescence markers but associated with enhanced kidney damage and fibrosis. In stress models, inflammatory cell infiltration was initially lower in knockout mice but later increased, leading to an accumulation of significantly more macrophages. SerpinB2 knockout tubular cells showed significantly reduced expression of the chemokine CCL2. Macrophages from knockout mice exhibited reduced phagocytosis and enhanced migration. Macrophage depletion and bone marrow transplantation experiments validated the functional relevance of these cell type–specific functions of SerpinB2. CONCLUSIONS: SerpinB2 influences tubule-macrophage crosstalk by supporting tubular CCL2 expression and regulating macrophage phagocytosis and migration. In mice, SerpinB2 expression seems to be needed for coordination and timely resolution of inflammation, successful repair, and kidney homeostasis during aging. Implications of SerpinB2 in human kidney disease deserve further exploration.